EXPLORING SELF-MEDICATION PRACTICE AMONG HEALTHCARE PROFESSIONALS: RISKS, PERCEIVED BENEFITS, AND CLINICAL IMPLICATIONS AT SHAHIDA ISLAM TEACHING HOSPITAL LODHRAN (The Research of Medical Science Review, 2025)
Background: Self-medication, the use of drugs without physician recommendation—is a growing concern globally, particularly among healthcare professionals (HCPs) who have medical knowledge, clinical experience, and unrestricted access to a variety of medications. While this practice may seem beneficial in terms of convenience, time-saving, and cost-effectiveness, it carries significant risks that cannot be overlooked. These include incorrect self-diagnosis, inappropriate drug selection, masking of underlying diseases, potential side effects, and the risk of drug abuse and dependency. Objective: The objective of this study was to evaluate how widespread the condition, patterns, influencing elements, and implications of self-medication trend among healthcare professionals, including nurses, doctors, and pharmacists, at Shahida Islam Teaching Hospital, Lodhran. Method: A cross-sectional study was done over six months using organized, closeended questionnaire. A stratified random sample of 61 healthcare professionals was surveyed. Data were evaluated using descriptive statistics to understand prevalence and trends. Results: The findings showed that 75.5% of respondents participated in selfmedication. Common reasons included cost-effectiveness (57.4%), accessibility to over the counter (OTC) drugs, and workplace stress. Minor ailments like vomiting (70.5%), acidity (62.3%), and wounds (57.4%) were frequently self-treated. Females and younger professionals (18–25 years) reported higher self-medication rates. Although 77.1% acknowledged the potential risks such as drug dependence Conclusion: Self-medication is prevalent among HCPs younger professionals (67.2%) and females (42.6%) were more likely to self-medicate despite their awareness of the associated risks. This calls for institutional policies, awareness programs, and educational interventions to encourage responsible practice and ensure both patient and provider safety.